Hubungan Antara Postur Kerja dengan Keluhan Gangguan Otot Rangka pada Tenaga Kerja Bongkar Muat (TKBM) di Pelabuhan Manado - Angelicha Putri Toli; Afnal Asrifuddin; Paul Artur Tennov Kawatu (Pusat Riset dan Inovasi Nasional, 2025)
Musculoskeletal disorders are disorders that occur in parts of the skeletal muscles experienced by individuals, ranging from painless to very painful complaints. Complaints of skeletal muscle disorders generally occur due to excessive muscle contractions due to excessive workloads with long loading durations. This study aims to determine the relationship between work posture and complaints of skeletal muscle disorders in stevedoring workers at Manado Port. The type of research used is quantitative with a cross-sectional study design. The research time was conducted from January to May 2025. The sample of this study was stevedoring workers at Manado Port with a total of 60 respondents. The results of the study using the Spearman correlation test showed that there was a relationship between work posture and complaints of musculoskeletal disorders with a p value of 0.000. The suggestion for Manado Port is that the port should provide information about body position while working to avoid complaints of musculoskeletal disorders, and workers and port management can work together to prevent musculoskeletal disorders through an, safe work training, and provision of adequate work facilities.